Sources of the invocations in the "House of Fame" - Solari, Marta Stella (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Literaturas Modernas, 1956)

(untitled)
Fil: Solari, Marta Stella. Universidad Nacional de Cuyo